The Effect of the Combustion Model on the Prediction of Temperature and Pressure - Gilberto Materano; Carlos Araujo; Numa Márquez; Alejandro Colman (Revista Técnica de la Facultad de Ingeniería, 2009)
A comparison of the temperature and pressure field obtained by the Adiabatic Chemical Equilibrium and the Generalized Finite Rate models, to simulate a twin-spool gas turbine”™s annular combustion chamber, is presented in this paper. The solution of the conservation equations was undertaken by using control volume method. In order to include the effect of the turbulence was used standard Kappa Epsilon model. The results obtained in this study show that the use of both models does not affect the pressure field prediction and the shape of the temperature profile at the outlet of the chamber. The same behavior is observed when the mass weighted temperature is calculated. For both models, this temperature was lower than the adiabatic flame temperature at the same operation conditions. By other hand, the most significant differences observed between the temperature fields given by both model, viewed in the axial and the exhaust plane, are observed when the variable reaches it maximum value.